DIAGNOSTIC ACCURACY OF CLINICAL SCORING SYSTEMS (NSS, NDS, AND TCSS) COMPARED TO ELECTROPHYSIOLOGICAL TESTING IN DIABETIC NEUROPATHY AMONG T2DM PATIENTS - Muhlisa, Safitri; Theresia Christin; Yulianto Kusnadi; Erial Bahar (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Diabetic neuropathy is one of the most common chronic complications in diabetes mellitus patients and can significantly impair quality of life. Early diagnosis is essential, but limited availability of diagnostic tools such as electrophysiological testing in many healthcare facilities calls for more practical and efficient alternatives. This study aimed to compare the diagnostic accuracy of three clinical scoring systems—NSS (Neuropathy Symptom Score), NDS (Neuropathy Disability Score), and TCSS (Toronto Clinical Scoring System)—in detecting diabetic neuropathy among Type 2 DM patients at Dr. Mohammad Hoesin Hospital, Palembang. A cross-sectional design was employed, and findings revealed that TCSS had the highest accuracy (90.3%) compared to NDS (85.5%) and NSS (85.4%). TCSS also demonstrated the best balance of sensitivity (95.4%) and specificity (77.8%). All three instruments can serve as effective early screening tools, especially in healthcare settings with limited access to electrophysiological diagnostic facilities.